“Butterfly Wings” stabilize Heptacene - Müller, Matthias; Rüdiger, Elias; Koser, Silke; Tverskoy, Olena; Rominger, Frank; Hinkel, Felix Peter; Freudenberg, Jan; Bunz, Uwe H. F. (Chemistry - a European journal, 2018)
The synthesis of bisalkynylated derivatives of tetrabenzo[a,c,p,r]heptacene and tetrabenzo[a,c,l,n]pentacene via two-/fourfold Stille reactions involving a 9-stannafluorene and suitable tetrabromoacenes is reported. These triphenylene-“winged” heptacenes are surprisingly stable and maintain a significant portion of the electronic properties of heptacenes.
Gesehen am 10.05.2019